MENUMBUHKAN KESADARAN DAN KEDISIPLINAN UNTUK MENGELOLA KEUANGAN DENGAN CARA MENABUNG PADA ANAK USIA DINI - Desi Ika Pratiwi (LPPM UIKA Bogor, 2022)
Student Community Service Activities are a form of student participation as a form of concernfor the surrounding community. This activity is in the form of counseling and the main target ischildren. The purpose of this activity is to educate and form a creative, innovative empowermentby utilizing used bottles into very useful items for children, as well as motivating children tolike to save from an early age. Saving has many benefits including practicing patience,preventing debt habits, increasing the number of emergency funds, and being reliable inmanaging finances. The habit of saving should be inculcated from a young age. It is intendedthat in later adulthood, they will become independent figures and not bother many people. Thiswill also make them less likely to get into debt. This activity was carried out at the TPA NurulHasanah, precisely in Pamulang, South Tangerang City. The method used in this activity isTheoretical Learning and Practical Learning which conveys the theory about saving and thepractice of making a piggy bank. Items that are very useful for children in saving are making apiggy bank.Keywords : Saving, Discipline, Creative, Innovative, Early childhood, Piggy bank.